The Copenhagen test and treat hepatitis C in a mobile clinic study: a protocol for an intervention study to enhance the HCV cascade of care for people who inject drugs (T'N'T HepC). Issue 11 (9th November 2020) - Lazarus, Jeffrey Victor; Øvrehus, Anne; Demant, Jonas; Krohn-Dehli, Louise; Weis, Nina
Abstract : Introduction: Injecting drug use is the primary driver of hepatitis C virus (HCV) infection in Europe. Despite the need for more engagement with care, people who inject drugs (PWID) are hard to reach with HCV testing and treatment. We initiated a study to evaluate the efficacy for testing and linkage to care among PWID consulting peer-based testing at a mobile clinic in Copenhagen, Denmark. Methods and analysis: In this intervention study, we will recruit participants at a single community-based, peer-run mobile clinic. In a single visit, we will first offer participants a point-of-care HCV antibody test, and if they test positive, then they will receive an HCV RNA test. If they are HCV-RNA+, we will administer facilitated referrals to designated 'fast-track' clinics at a hospital or an addiction centre for treatment. The primary outcomes for this study are the number of tested and treated individuals. Secondary outcomes include individuals lost at each step in the care cascade. Ethics and dissemination: The results of this study could provide a model for targeting PWID for HCV testing and treatment in Demark and other settings, which could help achieve WHO HCV elimination targets. The Health Research Ethics Committee of Denmark and the Danish Data Protection Agency confirmed (December 2018/January 2019) that this study did not require their approval. Study findings will be disseminated through peer-reviewed publications, conference presentations and social media.